Radiographic-anatomical aspects and gastrointestinal transit time in the spectacled caiman Caiman crocodilus crocodilus (Linnaeus, 1758) (Crocodylia, Alligatoridae) - Heloisa Castro Pereira; Juliana Macedo Magnino Silva; Líria Queiroz Luz Hirano; Luiz Martins da Silva Junior; André Luiz Quagliatto Santos (Biotemas, 2014)
In Brazil, there is increasing interest in the establishment of captive breeding programs for caiman. However, there is a paucity of in-depth studies on the proper care of these reptiles in captivity, particularly regarding optimal food type and frequency of feeding. The purpose of this study was to determine radiographic-anatomical aspects of, and gastrointestinal transit time of Caiman crocodilus crocodilus using contrast radiography. Ten caiman were used in the study, five males and five females, the animals were physically restrained for administration of a radiographic contrast medium, consisting of 10 ml/kg barium sulfate and mineral oil suspension (70%: 30% respectively), via the orogastric tube. Following contrast medium administration, radiographs were taken via dorsoventral projection first at five minutes, then at 6, 24, 30, 48, 54, 72, 80, 96, 104, 120, 130, 144 and 150 hours. This technique allows visualization of contrast medium passage through the GI tract, which enabled determination of gastrointestinal transit time in the spectacled caiman. The average time for contrast medium passage through the digestive tract of this species was 117 ± 29.6 h for females and 86.4 ± 21.5 h for males.